2013
DOI: 10.1609/aimag.v34i3.2486
|View full text |Cite
|
Sign up to set email alerts
|

Inquire Biology: A Textbook that Answers Questions

Abstract: L earning a scientific discipline such as biology is a daunting challenge. In a typical advanced high school or introductory college biology course, a student is expected to learn about 5000 concepts and several hundred thousand new relationships among them. 1 Science textbooks are difficult to read and yet there are few alternative resources for study. Despite the great need for science graduates, too few students are willing to study science and many drop out without completing their degrees. New approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
0
30
0
2
Order By: Relevance
“…We described how this approach generalizes to over 100 questions from a test suite. Empirical evaluation of the approach and its embedding into a student-centric instantiation of the AURA system such as Inquire (Chaudhri et al, 2013) remains an open problem for future work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We described how this approach generalizes to over 100 questions from a test suite. Empirical evaluation of the approach and its embedding into a student-centric instantiation of the AURA system such as Inquire (Chaudhri et al, 2013) remains an open problem for future work.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach based on suggested questions has been implemented in the intelligent textbook Inquire (Chaudhri et al, 2013), which uses AURA for question answering, and has been found to work effectively. The process interruption reasoning questions considered here are not yet available in Inquire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such is the project of companies like Knewton, who are working with publishers to embed adaptive tests into textbooks (Waters, 2014). Or, the other way around, questions and responses to questions can be used to direct you to places in a textbook (Chaudhri et al, 2013a). Advanced applications of these technologies include machine learning environments in which difficulty ranking of selected response items is crowdsourced based on patterns of response to particular questions in relation to student profiles (Segal, Katzir, Gal, Shani, & Shapira, 2014).…”
Section: Survey-psychometric Systemsmentioning
confidence: 99%